DESCRIPTION OF STUDENT SATISFACTION LEVEL AGAINST THE METHOD HYBRID LEARNING AT STIKES KARSA HUSADA GARUT - Hidayat, Dian Roslan; Rohadi, Dandi; Syswianti, Desy; Ramdani, Hasbi Taobah (Karsa Husada Health Institute Garut, 2023)
Over time, the number of Covid - 19 cases has decreased in several regions of Indonesia. This has caused several institutions to implement new policies to switch to hybrid learning methods, systems that use technology to integrate offline and online learning. Hybrid learning refers to a combination of face-to-face learning and online learning that forms a learning approach. Learning methods hybrid learning involving several factors, including students, lecturers, and networks. lecturers and students must understand the technology needed for hybrid learning, they also need to have a stable network to carry out hybrid learning methods so that students can avoid being left behind in the learning process. It is students in addition to adjusting to hybrid learning, students also still have to complete various coursework in order to get good grades and graduate on time, with changes in lecture methods that will affect the level of student satisfaction in the learning process. This research method is a quantitative research with the research design chosen is Quantitative Descriptive. In this study, quantitative descriptive was used to determine